CULTURE, PSYCHIATRY AND NEW ZEALAND - Chowdhury, A.N. (Medknow Publications, 2002)
This paper provides a critical appraisal of the importance of cultural perspective in the psychiatric diagnosis and management plan. The working philosophy of mental health services in New Zealand is primarily monocultural and based on Western medical conceptualisation of diagnosis and treatment protocol. In view of the emphasis on bicultural health perspectives in recent years and in tune with the objectives of the Treaty of Waitangi's ethnocultural partnership, the provision of a culturally safe and sensitive mental health coverage of Maori and Pacific Islander clients has become an important health issue in the country. The present discussion of the ethnocultural influence on clinical psychiatry highlights some of the relevant issues from the transcultural perspective.